Cameroon : 2010; Article IV Consultation; Staff Report; Debt Sustainability Analysis; Staff Report Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Cameroon. (IMF Staff Country Reports; Country Report ;, 2010)
Cameroon showed incipient signs of recovery from the global financial crisis. Although growth performance remained constrained under the Poverty Reduction Growth Facility (PRGF), tax and customs administrations were strengthened, macroeconomic stability was preserved, and debt relief under the Heavily Indebted Poor Countries (HIPC) and Multilateral Debt Relief Initiatives (MDRI) helped firm up debt sustainability. Executive Directors welcomed the new program aimed to accelerate growth through infrastructure development, development of rural and mining sectors, improvement in human resources, regional integration, and export diversification. They emphasized the need to maintain fiscal and financial stability to preserve economic growth.